Two birds with one stone: experiences of combining clinical and research training in addiction medicine. Issue 1 (December 2017) - Klimas, J.; McNeil, R.; Ahamad, K.; Mead, A.; Rieb, L.; Cullen, W.; Wood, E.; Small, W.
Abstract Background Despite a large evidence-base upon which to base clinical practice, most health systems have not combined the training of healthcare providers in addiction medicine and research. As such, addiction care is often lacking, or not based on evidence or best practices. We undertook a qualitative study to assess the experiences of physicians who completed a clinician-scientist training programme in addiction medicine within a hospital setting. Methods We interviewed physicians from the St. Paul's Hospital Goldcorp Addiction Medicine Fellowship and learners from the hospital's academic Addiction Medicine Consult Team in Vancouver, Canada (N  = 26). They included psychiatrists, internal medicine and family medicine physicians, faculty, mentors, medical students and residents. All received both addiction medicine and research training. Drawing on Kirkpatrick's model of evaluating training programmes, we analysed the interviews thematically using qualitative data analysis software (Nvivo 10). Results We identified five themes relating to learning experience that were influential: (i) attitude, (ii) knowledge, (iii) skill, (iv) behaviour and (v) patient outcome. The presence of a supportive learning environment, flexibility in time lines, highly structured rotations, and clear guidance regarding development of research products facilitated clinician-scientist training. Competing priorities, including clinical and family responsibilities, hindered training. Conclusions Combined training in addiction medicine and research is feasible and acceptable for current doctors and physicians in training. However, there are important barriers to overcome and improved understanding of the experience of addiction physicians in the clinician-scientist track is required to improve curricula and research productivity.